1991
DOI: 10.1557/jmr.1991.1404
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures of the melt-powder-melt-growth processed YBaCuO

Abstract: Microstructures of two MPMG processed YBaCuO materials with and without Y2BaCuO5 (211) inclusions were investigated by transmission electron microscopy. Using the MPMG process, it is possible to change the quantity of the 211 inclusions in the YBa2Cu3O7 (123) matrix. We prepared two YBaCuO samples with 0 and 30 vol. % 211 and with respective critical current density values of 2000 and 30 000 A/cm2 at 77 K and 1 T (magnetic field parallel to the c-axis). As possible pinning centers, we found stacking faults in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(21 citation statements)
references
References 6 publications
2
19
0
Order By: Relevance
“…Based on their transmission electron studies ͑TEM͒ they speculated that the clean and sharp Y 2 BaCuO 5 -YBa 2 Cu 3 O x interphase to be responsible for flux pinning. 41 However, this claim was not supported by other groups. [50][51][52][53] Based on the magnetization measurements, McGinn et al 50,51 reported a degradation of the critical current density with an increasing amount of Y 2 BaCuO 5 phase in zone-melted YBa 2 Cu 3 O x wires.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…Based on their transmission electron studies ͑TEM͒ they speculated that the clean and sharp Y 2 BaCuO 5 -YBa 2 Cu 3 O x interphase to be responsible for flux pinning. 41 However, this claim was not supported by other groups. [50][51][52][53] Based on the magnetization measurements, McGinn et al 50,51 reported a degradation of the critical current density with an increasing amount of Y 2 BaCuO 5 phase in zone-melted YBa 2 Cu 3 O x wires.…”
Section: Introductionmentioning
confidence: 88%
“…[23][24][25] In a high-T c superconductor various types of defects have been identified and claimed to be fluxpinning centers. [12][13][14] The defects observed in meltprocessed YBa 2 Cu 3 O x are twins, dislocations, 37,[43][44][45][46][47][48] stacking faults, [43][44][45] oxygen vacancies, Y 2 BaCuO 5 precipitates, [12][13][14][20][21][22][23][38][39][40][41][42][43][44][45] various other secondary phases, [46][47][48][49] etc. In particular, flux pinning by Y 2 BaCuO 5 precipitates has generated great interest in the superconducting community.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, uniform distribution of non-superconducting and inert inclusions such as of Y 2 BaCuO 5 (Y-211) is known to lead to effective flux pinning, without affecting the transition temperature. Enhanced surface area of fine-sized Y-211 inclusions, arising from large curvatures at their interface with the 123 matrix, gives rise to increased interfacial defect densities due to lattice mismatch [17]. Dopants like Y 2 O 3 [18], CeO 2 [19], ZrO 2 [13], BaCeO 3 [14], Al 2 O 3 [20], NiO [21], etc.…”
Section: Introductionmentioning
confidence: 99%